The Effect of Wilting on Proline Metabolism in Excised Bean Leaves in the Dark - Stewart, Cecil R. (1973)
The effects of wilting on the fate of proline and on the rates of nonprotein proline formation and utilization have been determined in excised bean leaves. Wilting did not alter the fate of exogenously added (14)C-l-proline (2 mm) in either non-starved leaves (from plants previously in the light) or starved leaves (from plants previously in the dark). The fate of proline in nonstarved leaves was protein synthesis and in starved leaves was protein synthesis and oxidation to other compounds. Wilting caused an increase in non-protein proline formation, possibly including release by proteolysis and synthesis from precursors in both starved and nonstarved leaves. Wilting caused a decrease in proline utilization in nonstarved leaves by decreasing protein synthesis. In starved leaves, wilting caused an increase in the rate of proline utilization but this is due to the higher content of proline in wilted leaves compared to the turgid leaves which causes more proline utilization by oxidation. Thus, the primary effects of wilting which lead to the accumulation of proline were to decrease protein synthesis and to increase proline formation. The source of the proline is not known but the increased formation due to wilting is not affected by the carbohydrate content of the leaf. The role of carbohydrates is to prevent the loss of accumulating proline by oxidation.